Insulinoma Presenting with Long-Standing Depression, Primary Hypogonadism, and Sertoli Cell Only Syndrome - Usman H. Malabu; Durgesh Gowda; Yong Mong Tan (Case Reports in Endocrinology)
The aim was to report an unusual case of insulinoma presenting with long-standing depression and primary testicular failure. We describe a 34-year-old male with clinical, laboratory, and radiologic data consistent with islet cell tumor and seminiferous tubule failure primary hypogonadism. The literature is reviewed relative to the component of this syndrome, and a possible association is discussed. The subject was investigated for a long-standing history of depression requiring medical attention because of mental confusion and slurred speech and was found to have an insulinoma. He was diagnosed with primary gonadal failure and physical examination showed no evidence of dysmorphic features. Chromosomal analysis revealed normal 46 XY and testicular biopsy showed Sertoli cell only syndrome (SCOS). Biochemistry revealed endogenous hyperinsulinism and histology confirmed an islet cell tumor. He remained euglycemic postoperatively and on followup. From this report, we emphasize drawing clinicians' attention to the possibility of an association between insulinoma and primary testicular failure and suggest consideration of this diagnosis in patients with hypergonadotropic hypogonadism who may present with infertility.